The Peak Flux of Long Gamma-Ray Bursts in the Ep,i–Liso Diagram and in the Classification - Guangxuan Lan; Jean-Luc Atteia (The Astrophysical Journal)
The E _p,i – L _iso correlation of long gamma-ray bursts (LGRBs) is regarded as a fundamental correlation for standardizing LGRBs to probe cosmology and constrain LGRB physics. However, this correlation may be affected by potential selection effects, which are likely overlooked in the current small LGRB redshift sample. In this work, we simulate a large LGRB sample that reflects the observed situation, aiming to study the impact of peak flux P on the observed LGRB E _p,i – L _iso correlation. We find that the overall E _p,i and L _iso distribution, which will directly affect the best-fit result of the correlation, is significantly dependent on the value of P . This indicates that the impact of peak flux selection should be carefully considered in the studies and applications of the E _p,i – L _iso correlation. Notably, we show that our simulated data can reproduce the observed P distribution only if some dependence between E _p,i and L _iso is included in the simulation. This is an indication that the E _p,i – L _iso connection is a crucial property of LGRBs. We also find that GRBs with high peak flux in the low- E _p,i and L _iso region are not the straightforward extrapolation of the GRB population in the higher- E _p,i and L _iso region. Selecting four bursts with L _iso ≤ 10 ^50 erg s ^−1 , E _p,i ≤ 10 ^2.5 keV, and P ≥ 10 ^0.5 ph cm ^−2 s ^−1 , we find two bursts, GRB 060614 and GRB 191019A, which may not be associated with the theoretical massive-star origin of LGRBs. This suggests that combining P with the position in the E _p,i – L _iso diagram may be used to indicate alternative LGRB origins.